SOCIO-ECONOMIC PROFILE OF MANIPURI PONY OWNERS* - Gupta, S.C.; Randhir Singh, TH (Indian Journal of Animal Production and Management, 2017)
A study was taken up to generate research based information on various socioeconomicprofiles of Manipuri Pony owners. During the survey, 215 Manipuri Pony ownersand farmers from 3 districts were interviewed using questionnaire. The study on varioussocio-economic parameters revealed that most of the pony owners belong to 15-55 yearsage group. About 76.74% of them had passed at least class VIII. In majority of the cases(62.33%), the holding size was 1 animal followed by 23.26% with 2 animals. The surveyalso revealed most of the owners (56.74%) were not having any land (landless) while32.56% maintained land up to 1 hectare. It was also known that Pony owners didn’t receiveany economic return from pony rearing at present unlike other livestock like dairy, poultry andpiggery. The survey further revealed that majority of the pony owners are economicallybackward and 59.92% of the pony owners depended for their livelihood on agriculture and allied activites